أثر حماية حقوق الملكية الفكرية على الحماية المقررة للمستهلك - والي, عبد اللطيف; بن يطو, أسامة (Revue jurisprudence; No 14 (2017): مجلة الاجتهاد القضائي, 2018)
يلتقي موضوعا حماية حقوق الملكية الفكرية وحماية المستهلك من خلال العديد من الجوانب، التي جعلت منهما حقلين خصبين لتأثر وتأثير كل منهما على الآخر، سواء من حيث التشريع أو التنظيم أو حتى من حيث طبيعة الحقوق التي يقررانها لأصحاب الإبداعات والمستهلكين على حد السواء، لاسيما إذا علمنا بأن محل حقوق الملكية الفكرية الذي هو في حقيقة الأمر مجموعة من الأعمال الفكرية أو الذهنية، التي غالبا ما تكون عبارة عن منتج أو سلعة أو خدمة موجهة للاستهلاك، وهو ما أثار التساؤل حول طبيعة هذا التأثر والتأثير؟ ومدى تأثير ذلك على مستقبل حماية كل موضوع على حدا؟ وعما إذا كانت هنالك موازنة بين الحقوق التي يقررانها؟ وعن إمكانية استحداث آليات معينة لإحداث هذه الموازنة مستقبلاً في حالة انعدامها في الوقت الحالي؟ . الكلمات المفتاحية : تأثير، حماية، حقوق، الملكية، الفكرية، المستهلك، الجزائري .   Abstract: The issue of the protection of intellectual property rights and consumer protection meet in many aspects, which made them fields of the vulnerability and the impact of each other, both in terms of legislation or regulation or even in terms of the nature of the rights that they determine the owners of innovations and consumers alike, and especially if we know that the intellectual property rights which is in fact a group of intellectual or mental works, which often is a product or a commodity or service addressed to the public consumers. And this is what the effects of the question on the nature of this vulnerability and impact? The extent of the impact on the future protection of each topic to an end? And about what if there was a balance between the rights which they determine? And about the possibility of the development of specific mechanisms for this balance in the future if it was lacking in the current time?. Keywords : Impact, Protection, Rights, Intellectual, property, Consumer, Algerian.